December dog - Roy, Ron, 1940- (Roy, Ron, 1940- Calendar mysteries, 2014)
After finding an unusual present-- a lost puppy-- on Christmas Eve, best friends Bradley, Brian, Nate, and Lucy scramble to find its owner before morning.